SEARCH FOR FACTORS MAINTAINING TERRICOLOUS BRYOFLORA RICHNESS IN ISOLATED HABITATS - THE CASE OF SCLEROPHYLLOUS OAK GROVES OF THE OCCIDENTAL BORDER OF THE MAURES MASSIF (VAR, FRANCE) - Hebrard, J P; Loisel, R (CRYPTOGAMIE BRYOLOGIE LICHENOLOGIE, 1994)
Processing (FAC) of 25 bryophytoecological releves and quantitative analysis of bryofloristical inventories from 4 forest structures (surface values respectively 3976, 6160, 13115 and 77617 m2) isolated within the vineyard near Pierrefeu-du-Var (siliceous substratum) show that, for what concerns sclerophyllous oaks ecosystems (Quercus ilex, more rarely Quercus suber), the more humid the local microclimate is, the greatest are richness and diversity of terricolous communities of bryophytes. The optimal conditions for preservation of richness in forest bryophytes are here realized at the Defens du Becasson (surface: 77617 m2, maximum width: 151 m), a north-facing side which is well protected against the drying action of dominant winds and where the architecture of the ligneous formations is heterogeneous. On the other hand, the diversity of available microhabitants in the 2 largest isolates (strong slope, presence of clearings and disturbed skirts) contributes to increase their global richness in bryophytes. Furthermore, the presence of a dense layer of shrubs limits the accumulation of dead leaves on soil surface, allowing a good spread of the bryophyte layer and correlatively an enrichment in forest taxa when ambient humidity is high enough.
APS
Keywords: bryophytes; Microhabitats; Quercus ilex; Quercus suber